The influence of anesthesia on prolongation of QTc interval in patients that underwent an open-heart surgery - Borzanović Sanja; Babić Rade (Medicinski Podmladak, 2020)
Introduction: Prolongation of QTc interval may cause cardiac electrical instability resulting in polymorphic ventricular tachycardia of the "torsades de pointes" type, as well as ventricular fibrillation and sudden death. It is known that anesthetics, laryngoscopy and tracheal intubation have various influences on QTc duration. Aim: The aim of this study was to determine the influence of anesthesia on prolongation of QTc interval in patients that underwent an open-heart surgery. Material and methods: The study enrolled 100 consecutive patients that underwent an open-heart surgery at a single cardiosurgical center. Standard institutional protocols for premedication, introduction and conduction of anesthesia were used. Correction of QT interval was calculated according to Bazzet's formula. For the assessments of the influence of premedication, anesthetics, operation type and tracheal intubation and extubation on QTc interval, ECG was taken at the following time points: baseline, after premedication, immediate postoperatively at admission to the intensive care unit, before extubation, immediately following extubation and a final following transfer to the general ward. As a cut-off value of QTc prolongation, values applied were > 450 ms for men and > 470 ms for women. Results: Out of 100 successive patients, 55 had postoperative prolongation of QTc. In this group, males were more prevalent (81.8%) in comparison to the group with normal QTc interval (64.4%; p = 0.049); average glycemic index was higher (7.6 mmol/l) in comparison to the group with normal QTc interval (6.5 mmol/l; p = 0.021) and average value of serum potassium was higher (4.5 mmol/l) in comparison to the group with normal QTc (4.1 mmol/l; p = 0.003). Conclusion: The association of applied anaesthesia with prolongation of QTc interval was affirmed.